Remoção dos corantes reativos azul 5G e remazol vermelho empregando o processo de adsorção - Canevesi, Rafael Luan Sehn (2015)
With the industrial growth achieved in recent years, there was a significant increase in the amount of industrial wastewater discharged into the environment, including, textile effluents rich in organic compounds of high molecular mass with characteristics toxic, carcinogenic and mutagenic. Therefore, it is necessary to develop methods for the treatment of effluents contaminated with dyes. The adsorption process has been largely employed in the treatment of industrial wastewater due to its low cost and efficiency at low concentrations. The system design of wastewater treatment by adsorption process on an industrial scale is required the use of a robust mathematical model based on phenomenological principles that describe efficiently the phase equilibrium data. This way, the main objective of this study was to investigate the adsorption of reactive dyes Remazol Red and Blue 5G, investigating the affinity of different adsorbents, the effect of pH and temperature, as well as obtaining the adsorption kinetics and equilibrium data in single-component systems and binaries, in order to get the optimum operation conditions. The bone char was the adsorbent with the highest removal capacity of reactive dyes. The effect of pH were studied in faixe 1-6 and the temperature in the range of 15 to 45 ° C jointly by the method of Delineation Central Composite Rotational (DCCR), only the pH of the initial solution had no effect on the dye adsorption capacity which proved favored by acidic pH. In order to characterize the adsrovente used to evaluate the effect of temperature and pH, as well, testing the kinetic and equilibrium were determined moisture, hydration capacity, surface area, pore size distribution and, density, morphology and chemical composition and surface charge. The models of Langmuir and Langmuir power can to describe with efficiency the kinetic and equilibrium single component data, while only the Langmuir model was efficient in binary data. The qmax values obtained for the dyes Blue 5G and remazol Red and binary in the temperature of 30 ºC and agitation of 100 rpm was 154.61, 144.71 and 161.81 mg g-1 respectively.